Targeted degradation of EGFR 19Del by PROTACs suppresses tumor growth in non-small-cell lung cancer - Piao, Lianhua; Gao, Ying; Su, Yangyang; Li, Qihui; Yuan, Xiaofeng; He, Wangqiu; Zhao, Wanzhou; Kulpakko, Janne; Cha, Pei-Chieng; Chang, Shan; Kong, Ren (Frontiers in Pharmacology, 2025)
ObjectThe occurrence of acquired resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) poses a significant challenge in treating non-small-cell lung cancer (NSCLC), limiting the clinical use of EGFR-TKIs. Proteolysis-targeting chimeras (PROTACs) demonstrate promise in preclinical settings. This study is aimed to design effective EGFR degraders by linking CRBN ligands with relatively lower molecular weights.MethodsComputational methods are employed to do the rational design for the PROTACs. Western blots are used to examine the expression of proteins including EGFR. Cell viability and colony-formation assays are conducted to evaluate the anti-proliferative effects of degraders to NSCLC cell lines, and apoptosis assays are assessed by Annexin V‐FITC/PI dual staining followed by flow cytometry. Female BALB/c nude mice bearing HCC827 xenografts are administered compound 14 (30 mg/kg) by intraperitoneal injection and the tumor volume and weights are measured.ResultsWe designed and synthesized a series of highly potent degraders based on the first‐generation EGFR‐TKI gefitinib and a cereblon (CRBN) ligand. Among these degraders, compound 14, with a relatively low molecular weight of 814.32 Da, exhibits notable activity against EGFRDel19 and EGFRL858R, with DC50 values of 0.26 nM and 20.57 nM, respectively, while showing no effect on EGFRwt. Additionally, downstream signaling pathways are significantly inhibited. Mechanistic studies indicate that EGFR degradation depends on the ubiquitin–proteasome system (UPS). Furthermore, compound 14 markedly suppresses the growth of HCC827 cells and induces apoptosis, with a 96‐h IC50 value of 4.91 nM, while not affecting the viability of H1299, HeLa, and H1975 cells up to 1 μM. In the HCC827 cell-derived xenograft model, compound 14 demonstrates substantial anti-tumor activity and effectively reduces EGFRDel19 protein levels in vivo.ConclusionWith its low molecular weight and excellent in vitro and in vivo efficacy, compound 14 could serve as a promising lead for developing degrader-based therapies targeting mutated EGFR.